Behind the Wheel of Epithelial Plasticity in KRAS-Driven Cancers - Arner, Emily N.; Du, Wenting; Brekken, Rolf A. (Frontiers in Oncology, 2019)
Cellular plasticity, a feature associated with epithelial-to-mesenchymal transition (EMT), contributes to tumor cell survival, migration, invasion, and therapy resistance. Phenotypic plasticity of the epithelium is a critical feature in multiple phases of human cancer in an oncogene- and tissue-specific context. Many factors can drive epithelial plasticity, including activating mutations in KRAS, which are found in an estimated 30% of all cancers. In this review, we will introduce cellular plasticity and its effect on cancer progression and therapy resistance and then summarize the drivers of EMT with an emphasis on KRAS effector signaling. Lastly, we will discuss the contribution of cellular plasticity to metastasis and its potential clinical implications. Understanding oncogenic KRAS cellular reprogramming has the potential to reveal novel strategies to control metastasis in KRAS-driven cancers.